IDENTIFIKASI SIFAT REKALSITRAN BENIH TANAMAN KENYEM (Lepisanthes alata (Blume) Leenh) - Lois Hintanara Shine Tanggara; Endang Pudjihartati (Agros Journal of Agriculture Science, 2024)
Kenyem seeds are seeds from forest plants, which are thought to be recalcitrant seeds. Proper seed handling based on seed properties can reduce the rate of seed deterioration and maintain seed quality. This study aims to determine (1) the recalcitrance level of kenyem seeds based on the physical and physiological characteristics of seeds and (2) desiccation sensitivity and minimum moisture content limit of kenyem seeds (Lepisanthes alata (Blume) Leenh). Identification of recalcitrant properties of kenyem seeds using the recalcitrant properties assessment method from Farrant, Pamenter, and Berjak (1988) and the protocol for determining seed storage behavior according to Hong and Ellis (1996). The results of the study showed that the recalcitrant properties of kenyem seeds were identified as medium recalcitrant according to Farrant et al (1988) and the seed storage behavior of recalcitrant seeds according to Hong and Ellis (1996). Drying of kenyem seeds has a desiccation sensitivity at a minimum moisture content limit of 48.87%. Drying the seeds to a moisture content of less than 48.87% will cause the seeds not to germinate. The optimal soaking water temperature for kenyem seeds is room temperature which results in a germination rate of 62.5% and a low vigor value compared to the 40°C soaking treatment. The DHL value of the P1 treatment showed the lowest value among the other treatments, indicating a high vigor and germination rate (DB) compared to the other treatments. Keywords: Recalcitrant seeds; Lepisanthes alata; Seed drying; Soaking INTISARIBenih kenyem merupakan benih dari tanaman hutan, yang diduga merupakan benih rekalsitran. Penanganan benih secara tepat berdasarkan sifat benih dapat menekan laju kemunduran benih dan mempertahankan mutu benih. Penelitian ini bertujuan untuk mengetahui (1) tingkat rekalsitran benih kenyem berdasarkan karakter fisik dan fisiologis benih dan (2) sensitivitas desikasi dan batas kadar air minimal benih kenyem (Lepisanthes alata (Blume) Leenh). Identifikasi sifat rekalsitran benih kenyem menggunakan metode penilaian sifat rekalsitran dari Farrant, Pamenter, dan Berjak (1988) dan protokol untuk menentukan perilaku penyimpanan benih menurut Hong dan Ellis (1996). Hasil penelitian menunjukkan bahwa Sifat rekalsitran benih kenyem diidentifikasi sebagai rekalsitran sedang menurut Farrant et al (1988) dan perilaku penyimpanan benih rekalsitran menurut Hong dan Ellis (1996). Pengeringan benih kenyem memiliki sensitivitas desikasi pada batas kadar air minimal 48,87%. Pengeringan benih hingga kadar air kurang dari 48.87%, akan menyebabkan benih tidak berkecambah. Suhu air perendaman yang optimal untuk benih kenyem yaitu suhu ruang yang menghasilkan daya berkecambah sebesar 62,5% dan nilai vigor yang rendah dibandingkan perlakuan perendaman suhu 40oC. Hasil nilai DHL perlakuan P1 menunjukkan nilai terendah diantara perlakuan-perlakuan lainnya, yang mengindikasi nilai vigor dan daya berkecambah (DB) yang tinggi dibandingkan perlakuan-perlakuan lainnya. Kata kunci: Benih rekalsitran; Lepisanthes alata; Pengeringan benih; Perendaman benih